PENGARUH PEMBERIAN POC LIMBAH SAYURAN DENGAN JENIS BERBEDA TERHADAP KELIMPAHAN Chlorella sp - Gusna Meli Roza; Rosyadi; Muhammad Hasby; Khairul Hadi (DINAMIKA PERTANIAN, 2022)
The aim of this study was to investigate the effect of liquid organic fertilizer obtained from vegetable waste on Chlorella sp. The study was conducted for 20 days at the Microalgae and Fish Nutrition Laboratory, Faculty of Agriculture, Islamic University of Riau, Pekanbaru. The study design used a completely randomized design (CRD) with 4 treatments and 3 replications, consisting of P1 = spinach, P2 = cabbage, P3 = katuk vegetables (Sauropus androgynous) and P = mustard greens. Liquid organic fertilizer at a dose of 2 cc/l was used in each treatment. The results showed that the best abundance of Chlorella sp cells in the treatment using mustard greens was 11,183,333 cells/ml, and the peak was on day 14, while the lowest cell abundance using vegetable waste was 6,166,667 cells/ml. The highest amount of biomass was in P4 (mustard green waste) 0.41 g/L and the lowest was in P3 (mustard green waste) 0.16 g/L.